Kooperatiflerde tasfiye işlemlerinin T. T. K, kooperatifler kanunu ve vergi kanunları açısından değerlendirilmesi ve uygulama örneği - Zelyurt, Serdal (My University, 2005)
Ülkemizde kooperatifler, belli bir amaç doğrultusunda, ortaklarının belli isteklerini kâr amacı taşımadan karşılama düşüncesi ile kurulan kuruluşlardır. Kooperatifler, kuruluş işlemlerini bu amaç doğrultusunda hazırladıkları ana sözleşmelerini tescil ve ilan ettirerek tamamlar ve tüzel kişilik kazanırlar. Ancak kooperatifler, bu amaçlarını birçok sebep ve nedenden dolayı gerçekleştiremez veya yerine getiremezler. Bu gibi durumlarda kooperatifin tüzel kişiliğine, yetkili organları tarafından veya ilgililer tarafından verilecek tasfiye kararı ile son verilmesi gerekir. Kooperatiflerin tasfiyesi, yasa veya ana sözleşmede yer alan sebeplerden birinin gerçekleşmesi ile, herhangi bir karar alınmadan kendiliğinden sona ermişse infisah, bunun tam tersi durumda yani yasa veya ana sözleşmede yer alan bir sebebe dayanarak yetkililer tarafından sona erdirilirse fesih şeklinde olacaktır. Her iki durumda da kooperatifin tasfiye edilmesi gerekecektir. Kooperatifin tüzel kişiliğinin sona ermesi halinde, malvarlığını hakkında düzenlenen işlemlerin tümüne tasfiye denilmektedir. Tasfiye ise, kooperatifin malvarlığının paraya çevrilmesi, alacaklarının tahsil edilmesi, borçlarının ödenmesi ve tasfiye kalanı olursa bunu ana sözleşme hükümlerine göre ortaklara dağıtılması ve kooperatifin kaydının ticaret sicilinden silinmesi işlemlerini kapsar. Hukuk sistemimizde kooperatiflerin tasfiyesini iki durumda incelenmiştir. Eğer kooperatif iflas sonucu tasfiye edilecekse iflasın tasfiyesi şeklinde, iflas harici durumlarda ise, Koop.K ve T.T.K'na göre tasfiye şeklindedir. Tasfiyenin vergisel boyutunu ise K.V.K'nu hükümlerine göre incelenmiştir. Bu tezde tasfiye sürecine girmiş bir kooperatifin tasfiye işlemlerine başlaması için yönetim kurulunun genel kurulu toplantıya çağırması, tasfiyenin yetkili organlar tarafından Ticaret Siciline tescil ve ilan ettirilmesi ile başlayan tasfiye işlemlerinin incelenmesinin yanında kooperatifin tasfiyeye başlama bilançosu, yevmiye kayıtları, büyük defter kayıtları, kesin mizanı, tasfiye sonu kapanış bilançosu ile kapanış kayıtları şeklinde uygulama örneği de yapılmıştır.

In our country, cooperatives are institution which are established, throughout a certain aim with the thought of meeting known desires of their associates without taking the aim of profit. Cooperatives complete procedures of establishmentby making basic contracts which they prepare with that aim registered and declared, and acquire legality on the other hand, cooperatives can not realize or carry out these targets because of lots reasons.In such conditions, it is necesarry to put on end to legality of the cooperative with the decision of liquidation which will be taken by authorized agencies of the cooperative or those concerned. If with the reality of one of the resons that takes place in law or main agreement, liquidation of cooperatives ends of its own accord without taking any decision, this will be in in the form of infisah. In the opposite side , that is, if liquidation of cooperatives is ended by the authorized at the base of one reason taking place in law or main agreement, this will be in the form of fesih. In these both situations, it will be necesarry to go into liquidationof the cooperative. On condition that the completion of legality of the cooperative,all the precedures which are put in order about real estade are called as liquidation. Liquidation includes procedures of excchanging real estade of the cooperative for money, left after the liquidation the precedure of distributing this between the associates according to the rules of main agreement and of deleting the entry of the cooperative from the register of trade. In our law system, the liquidation of cooperatives has been examined in two ways. If the cooperative goes into liquidation as a result of bankruptcy, the liquidation will be in the form of the liquidqtion of the bankruptcy, the cooperative will go into liquidation according to cooperative law and Turkish Commercial Code. The dimension of liquidation related to taxes is examined according to the decisions of corporation tax law. In this thesis report, besides the operations of the administrative committee's calling the general committee for meeting in order to start the liquidation precedures of one cooperative which has entered in liquidation processs, of examination of the liquidation precedures which take start when the liquidation is registered and declared to Trade Register by authorized agencies; the balance sheet of the cooperative related to its participation in liquidation, registration of great account boks or ledgers, definite scales, an done example of practice which is preparedin the shape of clesure balance and closure balance and closure registration being peculior to the end of the liquidation are also present.
Keywords: Kooperatifler